Singapore as a centre for international commercial litigation: Party autonomy to the fore - CHONG, Adeline (Institutional Knowledge at Singapore Management University, 2019)
This article considers two recent developments in Singapore private international law: the establishment of the Singapore International Commercial Court and the enactment of the Hague Convention on Choice of Court Agreements 2005 into Singapore law. These two developments are part of Singapore’s strategy to promote itself as an international dispute resolution hub and are underscored by giving an enhanced role to party autonomy. This article examines the impact of these two developments on the traditional rules of private international law and whether they achieve the stated aim of positioning Singapore as a major player in the international litigation arena.